THE EFFECTIVENESS OF USING COMMUNICATIVE LANGUAGE TEACHING (CLT) TECHNIQUES ON STUDENTS’ SPEAKING SKILL - Lely Khusnul Khowatim; Achmad Farid; Muhammad Saifuddin (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
Communicative language teaching is a helpful technique because it focuses on developing four language and communication dependent skills. This Research was to examine the effectiveness of using communicative language teaching on student’s speaking skill. To obtain the data, quantitative research was used. The data were gotten by statistic test. The sample in the study, there are two groups, namely, the experimental group and the control group. The experimental group was taught using role play and pair work, and the control group was taught using traditional method. Experiment research was carried out using pre test and post test design to determine whether there was any significant difference between the scores of the experimental and control groups. Current findings the study showed that the experimental group scored higher than the control group. This finding has positive implications for the continuation of teaching practices for teachers.